1979
DOI: 10.1098/rstb.1979.0025
|View full text |Cite
|
Sign up to set email alerts
|

The natural regulation of giant tortoise populations on Aldabra Atoll: recruitment

Abstract: The reproductive ecology of the giant tortoise ( Geochelone gigantea Schweigger) in three isolated populations was studied for 2 years on Aldabra Atoll. Density-dependent recruitment was demonstrated. Nest destruction in the low density area was dependent on the density of mature females providing a mechanism for regulating population size. Increases in annual rainfall and the resultant increase in food availability induced an increase in mean egg mass in the low density area (and there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
43
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 13 publications
8
43
0
Order By: Relevance
“…The same was also observed for Geochelone elephantopus (MacFarland et al, 19746) and Geochelone gigantea (Swingland & Coe, 1978). Since temperature is the variable most affecting incubation of rigid-shelled turtle eggs (Packard et al, 1981;Packard, Packard & Boardman, 1982;Janzen, 1993a), the observed variation is very likely to reside in the different thermal environments experienced by clutches laid at different moments of the two-month nesting season.…”
Section: Hatching and Emergencesupporting
confidence: 66%
See 1 more Smart Citation
“…The same was also observed for Geochelone elephantopus (MacFarland et al, 19746) and Geochelone gigantea (Swingland & Coe, 1978). Since temperature is the variable most affecting incubation of rigid-shelled turtle eggs (Packard et al, 1981;Packard, Packard & Boardman, 1982;Janzen, 1993a), the observed variation is very likely to reside in the different thermal environments experienced by clutches laid at different moments of the two-month nesting season.…”
Section: Hatching and Emergencesupporting
confidence: 66%
“…The delay of emergence in Testudo graeca hatchlings is likely to be mediated by the absorption of external yolk sacs, which the new-borns still carry upon hatching, as has been observed in Gopherus polyphemus (Linley & Mushinsky, 1994) and Geochelone gigantea (Swingland & Coe, 1978). One T. graeca hatchling removed from the nest after hatching also carried a yolk sac weighing 11% of its body weight.…”
Section: Hatching and Emergencementioning
confidence: 89%
“…Anecdotal reports have suggested that capture and/or ingestion of larger turtles may be difficult for certain predators (Barrows and Schwarz 1895, Bustard 1979, Swingland and Coe 1979. A more likely explanation, however, is differential exposure to predation.…”
Section: Size-dependent Selection: Possible Causesmentioning
confidence: 95%
“…Applications of Egg-Size Reduction to Other Groups.-Offspring size is correlated with determinants of offspring fitness in many groups including fish (Bagenal, 1969;Henrich, 1988), amphibians (Kaplan, 1980), reptiles (Ferguson and Fox, 1984;Swingland and Coe, 1979), and insects (Richards and Myers, 1980;Wiklund and Persson, 1983;Karlsson and Wiklund, 1984;Steinwascher, 1984). However, there have been few direct experimental tests demonstrating the causal relationships that link maternal investment (eggsize, yolk volume, etc.)…”
Section: Discussionmentioning
confidence: 99%